Hemophagocytic Lymphohistiocytosis Secondary to Malignancy and Chemotherapy in Pediatric Patients: A Single-Institution Experience - Haloot, Justin; Kaheri, Mahdi; Hamby, Tyler; Ray, Anish (Indian Journal of Medical and Paediatric Oncology, 2019)
Hemophagocytic lymphohistiocytosis (HLH) is an uncommon yet potentially devastating systemic disease, arising from uncontrolled activation of the immune system. While the primary form of this disease can be caused by genetic mutation(s), the secondary form may be triggered by infection and hematologic, malignant, and metabolic conditions. The diagnosis of HLH remains a clinical challenge due to nonspecific symptoms. Proper diagnosis is significantly more difficult among patients with acute leukemia who have received chemotherapy. The objective of this study is to describe three unique cases of secondary HLH, describe the specific treatment, and improve the awareness of this condition. Two patients with acute myeloid leukemia (AML) and one with acute lymphoblastic leukemia were diagnosed with HLH, having fulfilled the criteria as outlined in the HLH-2004 protocol. They then received HLH-specific treatment. Two patients passed – one from refractory HLH and one from primary disease (i.e., AML) – and one patient remains alive 22 months after her allogeneic bone marrow transplant. The diagnosis of HLH requires the presence of any five of the eight criteria. Due to its heterogeneous presentation, it remains imperative that treating clinicians remain cognizant about HLH so that prompt diagnosis may allow appropriate treatment.
Keywords: Acute leukemia; ferritin; hemophagocytic lymphohistiocytosis